PENGUATAN KARAKTER KEWIRAUSAHAAN MELALUI OUTBOUND TRAINING DALAM MEWUJUDKAN DESA WISATA TUGU SELATAN SEBAGAI DESTINASI UNGGULAN - Inna Hanarti; Dingot Hamonangan Ismail; Aditya Burhan; Rahmi Utami; Harry Jundrio (POLITEKNIK LP3I JAKARTA, 2025)
Tugu Selatan Village has great potential as a leading tourist destination in Puncak, West Java. However, the main challenge lies in the mental readiness and character of MSMEs in facing global competition. This article discusses the Community Service (PkM) program, a collaborative effort between six universities and a Village-Owned Enterprise (BUMDes). One innovative method used is outbound training to hone teamwork, leadership, and mental toughness. The results show that the experiential learning approach effectively increases the motivation and collaborative character of entrepreneurs in Kampung Koboi and Kampung Susu.